2021
DOI: 10.3390/antiox10060825
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Carrichtera annua DC. Ethanolic Extract Counteracts Cisplatin Triggered Hepatic and Renal Toxicities

Abstract: Cisplatin is a powerful anti-neoplastic drug that displays multi-organ toxicity, especially to the liver and kidneys. Consumption of phytomedicines is a promising strategy to overcome the side effects of chemotherapy. Carrichtera annua extract proved to possess potent antioxidant activity. Its protective potential against cisplatin-induced hepato–nephrotoxicity was scrutinized. Moreover, a phytochemical study was conducted on C. annua ethyl acetate fraction which led to the isolation of five known phenolic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…In a continuing effort to discover biologically active phytochemicals from medicinal plants [21][22][23][24][25], our group focused on the study of T. sanguinea, a locally well-known medicinal plant widely distributed throughout the forest zones of tropical Africa. T. sanguine is rich in phenolic compounds, such as brevifolin carboxylic acid and gallic acid [26].…”
Section: Introductionmentioning
confidence: 99%
“…In a continuing effort to discover biologically active phytochemicals from medicinal plants [21][22][23][24][25], our group focused on the study of T. sanguinea, a locally well-known medicinal plant widely distributed throughout the forest zones of tropical Africa. T. sanguine is rich in phenolic compounds, such as brevifolin carboxylic acid and gallic acid [26].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from this, it reacts with hydrogen peroxide and organic peroxides to show antioxidant effect [31,32]. Previous studies show that decrease in GSH levels result in doxorubicin and cisplatin associated heart [33,34], liver [33,35], kidney [33,35] and [36,37] damage. The decrease in tGSH levels in ovarian, heart, liver and kidney tissues of the doxorubicin and cisplatin given rats in our study supports the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies showed that overproduction of reactive oxygen species induces the synthesis of proin ammatory cytokines and causes tissue damage [8,33,35]. LPO associated oxidative stress increases the production of TNF-α and IL-6 to increase tissue damage [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Since oxidative stress, inflammation, and apoptosis are the main mechanisms by which MTX induces toxicity and causes the loss of spermatocytes, as well as the atrophy of seminiferous tubules [ 70 ], agents that have antioxidant, anti-inflammatory, and antiapoptotic effects would be beneficial to ameliorate such germ cell toxicity. Many plants are the main sources for bioactive compounds that can be used to relieve diseases [ 81 ]. For instance, phytomedicine and plant-derived antioxidants are considered a prosperous strategy for alleviating chemotherapy-induced organ toxicities [ 28 , 82 , 83 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%